2022
DOI: 10.1097/gox.0000000000004308
|View full text |Cite
|
Sign up to set email alerts
|

Is Surgery Needed for Diplopia after Blowout Fractures? A Clarified Algorithm to Assist Decision-making

Abstract: Background: Diplopia is a common symptom after blowout fractures, with an incidence of 43.6%-83%. Although there is some consensus toward surgical correction, diplopia is not always resolved by surgery. Thus, there is a clinical dilemma for surgeons with regard to performing surgery at a specific time. This review aimed to create an algorithm to support accurate and effective decision-making. Methods: We reviewed articles published on PubMed during 2013-2020 regarding orbital fractures. Articles discussing sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(200 reference statements)
0
2
0
Order By: Relevance
“…In fractures involving more than half of the orbital floor, there is also the possibility of the hypoglobus likewise resulting to diplopia [2,16]. Retrospective studies published within the past decade have reported on the incidence of diplopia caused by orbital blowout fractures to be ranging from 20% to as high as 83% [11,12,18]. However, these studies did not indicate the presence of strut fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fractures involving more than half of the orbital floor, there is also the possibility of the hypoglobus likewise resulting to diplopia [2,16]. Retrospective studies published within the past decade have reported on the incidence of diplopia caused by orbital blowout fractures to be ranging from 20% to as high as 83% [11,12,18]. However, these studies did not indicate the presence of strut fractures.…”
Section: Discussionmentioning
confidence: 99%
“…A spontaneous clinical improvement in patients conservatively treated for orbital blowout fractures has been documented in the literature [11,12]. However, the significance of the inferomedial orbital strut in preventing fracture-related symptomatic diplopia has yet to be established.…”
Section: Introductionmentioning
confidence: 99%